Effects of metals on freshwater microcrustaceans. Metodological advances and potentiality of cladocerans and copepods as test organisms - Gutierrez, María Florencia (2011)
The increase of metals in fresh water systems due to anthropogenic activities cause important alterations on the biota. The present review analyze the adverse effects of various metals of ecotoxicological relevance on microcrustaceans zooplankton species (cladocerans and copepods), the experimental advances and the advantages of each group as test organisms. In general, the need to obtain more sensitive and representative indicators than the tradicional ones leads to subchronic, interespecific and multigenerational studies. Additionally, the analysis of mixtures as well as their indirect effects allows to acquire more integral knowledges of the impact of contaminants. The toxic effects are different, depending on the nature of metals, the physicochemical characteristics of the water, exposutre time and genetic traits. However, most works are focused on few species, leading vacant areas on the knowledge of the representatives of every particular region. Despite some cladocerans and copepods atributes make them good bioindicators (size, morphology and ecological role), differences of development, reproduction and perpetuation strategies bring advantages to one group on another.